Analysis of Civics Subjects in Preventing Cyberbullying Behavior Due to Moral Decadence in the Digital Age - Gita Puspita Sari; Syifa Fauziah; Masna Bonita Hutabarat; Sintya Rodiani Makmur; Muhammad Mikdad; Rama Wijaya Abdul Rozak; Nisrina Nurul Insani (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study aims to find out the role of Pancasila and Citizenship Education (PPKn) taught by Pancasila and Citizenship Education Teachers at SMK Negri 1 Majalaya in overcoming the phenomenon of cyberbullying. This research uses descriptive qualitative method. The informants consisted of 35 students and 2 Pancasila and Citizenship Education Teachers from SMK Negeri 1 Majalaya. This study uses structuration theory from Anthony Giddens which states that globalization has changed most of the ways of human life which have certain consequences, including the moral degradation of students as a result of advances in information and communication technology, namely the phenomenon of cyberbullying. The data analysis technique used is Data Tabulation, Data Description and Analysis. The results of this study indicate that there are still many students at SMKN 1 Majalaya who experience cyberbullying both through social media and online games. As well as Pancasila and Citizenship Education Teachers at SMKN 1 Majalaya have been aware of this cyberbullying phenomenon and are trying to teach and instill Pancasila values to their students to be able to provide prevention of cyberbullying by making students at SMKN 1 Majalaya wiser in using the internet, bearing in mind that Pancasila Education and Citizenship is also very important in the formation of a nation and character building that forms citizens who are able to think critically and act responsibly.